Factors Influencing E-Commerce Adoption in Food and Beverage MSMEs: An Extended TAM Approach With Trust and Perceived Risk - Muhammad Awaluddin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The rapid growth of digital technology has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector to expand their market reach through e-commerce platforms. However, adoption remains uneven, with many businesses still reluctant to fully integrate digital tools into their operations. This study aims to examine the determinants of e-commerce adoption using an extended Technology Acceptance Model that incorporates trust and perceived risk. A quantitative survey design was employed, with data collected from 210 valid responses of food and beverage MSME owners and managers in Indonesia. Data analysis confirmed the validity and reliability of the measurement model and tested the hypothesized relationships among variables. The results show that perceived usefulness, perceived ease of use, and trust significantly influence behavioral intention, while perceived risk has no significant effect. Furthermore, both behavioral intention and attitude toward use positively affect actual usage of e-commerce platforms. The extended model explains a substantial proportion of the variance in behavioral intention (62.8%) and actual usage (55.9%). These findings provide theoretical contributions by validating the extended TAM framework in the MSME context and practical implications for policymakers, platform developers, and business owners. Enhancing perceived usefulness through training, improving ease of use through user-friendly design, and strengthening trust via secure systems are critical strategies for accelerating digital adoption.